SERTÃO DO VALONGO: ARTICULAÇÃO DE LIBERDADE, RELIGIÃO E IDENTIDADE EM UMA COMUNIDADE QUILOMBOLA ADVENTISTA - MOURA FILHO, Antonio Braga de (2015)
There is a growing interest in academic research, as well as in official policies aimed at reducing social inequalities in order to deepen the studies on the remaining of slaves who reside today as Maroons throughout Brazil. In recent decades, seeking in various ways, to redress historic wrongs committed against the descendants of the people of African origin living in the country. My research focused to gaze at these tiny communities, the Hinterland of Valongo, whose territory is located in a narrow strip of land in the interior of Santa Catarina, officially recognized as a remnant of the old Maroons since 2004. The dwellers of Valongo has attracted the attention of scholars and curious who come in contact with them and the reason for this interest is connected particularly to a specificity only found there: they are practitioners of the Adventist belief for nine decades and this peculiarity attracts studies that seek to investigate the way of living of these people, closely linked to the practice of the religion. The study is a qualitative research, of bibliographic character, and has as its theoretical reference the Critics of Sociology by Florestan Fernandes. In this study, I reflected on the ideals of freedom present in the genesis of the community in the late 19th century; I analyzed the aspects of the strong influence of religion for its residents from the group conversion to Adventism in the 1930s; I discussed how the freedom and religion are linked to the construction of the identity of these people over time, making the little world of the inhabitants of Valongo a provocative space of reflections.